Concept for assessing productrelated pesticide footprint - M?ller, K.; Deurer, M.; Northcott, G.; Clothier, B.E. (New Zealand Plant Protection, 2010)
Increased environmental awareness has motivated retailers to label products with carbon footprints This allows consumers to choose products according to their global warming potential Public concern is also targeting pesticides Heightened customer sensitivity to residues has already led to a ban on using certain pesticides by European retailers A tool is needed for assessing the environmental impact of pesticides used for producing a specific product This paper introduces the concept of the pesticide footprint (PFP) which fills this gap by estimating the total loss of pesticides and their respective impact on humans and ecosystems per product unit in a lifecycle framework The impact assessment considers how these losses affect humans through the consumption of the product containing residues and ecosystems through the exposure to residues in the environment The PFP includes the production of the pesticide its application in the orchard and the final disposal of waste